Influence of Blending of Nonionic Emulsifiers Having Various Hydrophilic Head Sizes on Lipid Oxidation: Investigation of Antioxidant Polarity-Interfacial Characteristics Relationship - Jiyun Lee; Seung-Jun Choi (MDPI AG, 2021)
The purpose of this study was to deliver insights into the effect of interfacial composition and antioxidant polarity on the lipid oxidation of emulsions. Emulsions were created using blends of nonionic ethoxylated fatty acid alcohol surfactants with different hydrophilic head sizes, and lipophilic (TBHQ) and amphiphilic (lauryl gallate) antioxidants were incorporated into the emulsions. At the same surfactant concentration, emulsion stabilized with surfactant with a smaller hydrophilic head was more susceptible to lipid oxidation than that stabilized with surfactant with a larger hydrophilic head. When surfactants with a similar hydrophilic head size were used, lipid oxidation in emulsion containing more surfactant was slightly faster than that containing less surfactant. When emulsions were created with a 1:1 molar ratio mixture of surfactants with small and large hydrophilic heads, surfactant concentration (1.00 and 2.932 mM) had little effect on lipid peroxide generation rate. However, the concentration of thiobarbituric acid-reactive substances (TBARSs) in the emulsion prepared at 1.00 mM increased faster than that prepared at 2.93 mM. Alteration of interfacial composition and surfactant concentration did not affect antioxidant ability, regardless of antioxidant polarity, to inhibit lipid peroxide generation. However, the ability of lauryl gallate and TBHQ to prevent TBARS generation was elevated by mixing surfactants with small and large hydrophilic heads and by decreasing surfactant concentration. In most emulsions, lauryl gallate showed a more effective antioxidant ability than TBHQ.